Construction method of self-repairing waterproof composite coating for building outer wall and composite coating
Patent Information
- Application Number
- CN202611387505.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-13
AI Technical Summary
[0003]然而,现有技术中的建筑外墙防水材料及施工方法在实现长效防护与自主修复的协同控制方面仍存在显著缺陷
[0034]本发明通过基层粘结增强层中水性环氧树脂乳液与硅烷偶联剂、纳米二氧化硅的协同作用,实现了与混凝土基层的高强粘结与毛细渗透锚固,为复合涂层提供稳定的附着基础;自修复防水主层中水性聚氨酯乳液与可降解壳聚糖微胶囊、形状记忆聚氨酯弹性体的双重自修复体系协同,第一重微胶囊即时修复针对宽度≤0.5mm裂缝实现快速密封,单次裂缝面积闭合率≥90%;第二重形状记忆效应修复在自然环境温度下即可触发,针对宽度≤1.0mm裂缝实现可重复多次修复,裂缝面积闭合率≥85%,突破传统单一自修复技术仅能单次修复且需外部触发条件的局限,同时纳米蒙脱土的引入增强了涂层的阻隔性能与力学强度;
Smart Images

Figure CN122898191A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of building exterior wall waterproofing and protection technology, specifically to a construction method and a composite coating for a self-healing waterproof composite coating for building exterior walls. Background Technology
[0002] Self-healing waterproof composite coating for building exterior walls is a protective system applied to building exterior walls. Its core is to resist the effects of natural environment such as wind and rain erosion, temperature changes, ultraviolet radiation, and acid and alkali corrosion through the multiple protective mechanisms of the coating material, so as to prevent the wall from developing defects such as cracks, hollows, and leaks, thereby ensuring the integrity of the building's appearance, extending the service life of the structure, and eliminating safety hazards.
[0003] However, existing building exterior waterproofing materials and construction methods still have significant shortcomings in achieving synergistic control of long-term protection and self-repair.
[0004] Firstly, while microcapsule-based self-healing materials can repair cracks, their limited repair agent reserves only allow for single or a few repairs, making it difficult to meet the long-term service requirements of building exterior walls. Shape memory polymer-based self-healing materials rely on external conditions such as high temperatures for triggering and cannot achieve self-repair in natural environments. Traditional roll waterproofing is complex to install and prone to leakage at joints; coating waterproofing lacks sufficient crack resistance and is susceptible to irreversible cracks due to substrate deformation after long-term use; mortar waterproofing has poor flexibility and cannot withstand substrate expansion and contraction. While some self-healing coatings possess some repair capabilities, they often lack sufficient waterproofing, weather resistance, and adhesion, resulting in insufficient bonding strength with the substrate and a tendency for blistering and detachment.
[0005] Meanwhile, existing exterior wall waterproofing construction methods suffer from problems such as cumbersome procedures, insufficient targeted treatment of the substrate, low precision in coating thickness control, and non-standard joint treatment, which greatly reduce the overall protective effect of the waterproof coating and make it difficult to fully utilize the performance advantages of waterproof materials.
[0006] In summary, existing building exterior wall waterproofing materials and construction methods have shortcomings in terms of self-repair capability, long-term waterproofing performance, multi-functional synergy, and refined construction control, which restricts the development of exterior wall protection systems towards higher durability, higher reliability, and lower maintenance costs. Summary of the Invention
[0007] The purpose of this invention is to improve the formulation system and construction method of existing building exterior wall waterproofing materials in order to achieve the integration of long-term repair and multi-functional synergy.
[0008] The purpose of this invention is to provide a construction method and a composite coating for a self-healing waterproof composite coating for building exterior walls. Through the organic integration of a three-layer composite structure and a dual self-healing mechanism, combined with refined base treatment and precise control of construction technology, a multi-functional synergy is achieved throughout the entire process from material formulation to construction, significantly improving the self-repair capability, long-term protective performance and construction quality reliability of the building exterior wall waterproofing system.
[0009] To achieve the above objectives, the present invention aims to provide a self-healing waterproof composite coating for building exterior walls. The composite coating, from the inside out, comprises a base bonding reinforcement layer, a self-healing waterproof main layer, and a weather-resistant protective surface layer.
[0010] The base bonding reinforcement layer comprises the following raw materials in parts by weight:
[0011] 30-40 parts of waterborne epoxy resin emulsion, 2-4 parts of silane coupling agent, 3-5 parts of nano silica, 25-35 parts of cement-based filler, 0.5-1 part of defoamer, 1-2 parts of film-forming aid, and 15-25 parts of deionized water.
[0012] The self-healing waterproof base layer comprises the following raw materials in parts by weight:
[0013] The composition includes: 40-50 parts of waterborne polyurethane emulsion, 8-12 parts of biodegradable chitosan microcapsules with a particle size of 100-200μm, 5-8 parts of shape memory polyurethane elastomer, 4-6 parts of nano-montmorillonite, 2-3 parts of polyethylene glycol diglycidyl ether, 0.5-1 part of UV stabilizer, 0.3-0.8 parts of defoamer, and 10-15 parts of deionized water.
[0014] The weather-resistant protective surface layer comprises the following raw materials in parts by weight:
[0015] 35-45 parts fluorocarbon emulsion, 3-5 parts nano titanium dioxide, 0.5-1 part anti-aging agent, 1-2 parts film-forming aid, 5-8 parts pigment, and 20-30 parts deionized water.
[0016] As a further improvement to this technical solution, the thickness of the base bonding reinforcement layer is 0.3-0.5mm, the bonding strength is ≥2.5MPa, and the water-resistant bonding strength is ≥2.0MPa.
[0017] As a further improvement to this technical solution, the thickness of the self-healing waterproof main layer is 1.5-2.5mm, the elongation at break is ≥500%, the seepage resistance pressure is ≥1.2MPa, and the low-temperature flexibility is -20℃ without cracks.
[0018] As a further improvement to this technical solution, the thickness of the weather-resistant protective surface layer is 0.4-0.6mm, the total thickness of the composite coating is 2.2-3.6mm, it can withstand artificial weathering for 1000h without powdering or cracking, it can withstand acid and alkali corrosion immersion for 72h without qualification, and the surface water absorption rate is ≤3%.
[0019] The second objective of this invention is to provide a construction method for the aforementioned self-healing waterproof composite coating for building exterior walls, comprising the following steps:
[0020] Step S1: Construction preparation, weigh the materials for each layer according to the mass fraction, stir each layer of materials evenly, and let stand to remove air bubbles;
[0021] Step S2: Base layer pretreatment, clean the base layer surface, treat cracks and holes, and apply base treatment agent after the base layer is dry;
[0022] Step S3: Composite coating construction, the base bonding reinforcement layer, the self-healing waterproof main layer and the weather-resistant protective surface layer are constructed in sequence. The self-healing waterproof main layer is sprayed in two coats, and fiberglass cloth is added to the joints for reinforcement.
[0023] Step S4: Maintenance and acceptance. After the construction is completed, maintenance shall be carried out, and the equipment shall be put into use after passing the acceptance.
[0024] As a further improvement to this technical solution, in step S1, the settling time is 5-10 minutes, the prepared material must be used up within 1 hour, and the self-healing waterproof main layer material must be used up within 2 hours.
[0025] As a further improvement to this technical solution, in step S2, a high-pressure cleaner is used to rinse the surface of the base layer to remove loose soil, oil stains, release agent and loose attachments, and the parts with a protrusion height > 3mm are cut and ground flat.
[0026] When the crack width is <0.3mm, apply the base bonding reinforcement layer directly to penetrate and seal it; when the width is ≥0.3mm, chisel a V-shaped groove and fill it to reinforce it.
[0027] When the diameter of the hole is less than 50mm, it should be filled in layers with polymer cement mortar. When the diameter is greater than or equal to 50mm, steel bars should be inserted before repair.
[0028] As a further improvement to this technical solution, in step S3, the base bonding reinforcement layer is applied by roller in a crisscross pattern, with the thickness controlled at 0.3-0.5 mm.
[0029] The self-healing waterproof main layer is applied using a special spray gun, with a thickness controlled at 1.5-2.5mm. It is applied in two coats, with an interval of 4-6 hours between the two coats.
[0030] After the self-healing waterproof main layer has fully dried, the weather-resistant protective top layer is applied by roller coating, with a thickness controlled at 0.4-0.6mm. It is applied in two coats, and the thickness is monitored in real time using a wet film thickness gauge during the application process.
[0031] As a further improvement to this technical solution, in step S3, an additional layer of 200g / m² alkali-free glass fiber cloth is laid at the door and window openings and the base of the parapet wall, with an overlap width of ≥100mm.
[0032] As a further improvement to this technical solution, in step S4, the curing period adopts a dry-wet alternation curing method of natural curing for the first 2 days and watering twice a day for the next 5 days; the acceptance criteria are that there are no cracks, hollows, or missed coatings in the appearance, the thickness deviation is ±0.2mm, the bonding strength is ≥2.0MPa, and the anti-seepage pressure is ≥1.0MPa.
[0033] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0034] This invention achieves high-strength adhesion and capillary penetration anchoring with the concrete substrate through the synergistic effect of waterborne epoxy resin emulsion, silane coupling agent, and nano-silica in the base bonding reinforcement layer, providing a stable adhesion foundation for the composite coating. In the self-healing waterproof main layer, the waterborne polyurethane emulsion, biodegradable chitosan microcapsules, and shape memory polyurethane elastomer form a dual self-healing system. The first layer of microcapsule immediate repair achieves rapid sealing for cracks ≤0.5mm in width, with a single crack area closure rate ≥90%. The second layer of shape memory effect repair can be triggered at natural ambient temperature, enabling repeated repair for cracks ≤1.0mm in width, with a crack area closure rate ≥85%. This breaks through the limitations of traditional single self-healing technology, which can only repair once and requires external triggering conditions. At the same time, the introduction of nano-montmorillonite enhances the barrier properties and mechanical strength of the coating.
[0035] The combination of fluorocarbon emulsion and nano-titanium oxide in the weather-resistant protective surface layer endows the coating with excellent resistance to UV aging, chemical corrosion, and self-cleaning functions, effectively protecting the inner structure. The three-layer structure complements each other's functions and provides progressive protection. Finally, through alternating dry and wet curing and rigorous acceptance testing, the final forming quality and long-term service performance of the coating are guaranteed. This invention fundamentally overcomes the technical difficulties of existing exterior wall waterproofing technologies, such as insufficient crack resistance, inability to self-repair, and lax construction control, leading to frequent leaks and high maintenance costs. It extends the service life of the composite coating to more than 15 years and successfully prepares a self-healing waterproof composite coating for building exterior walls that meets the requirements of high durability and high reliability. Attached Figure Description
[0036] Figure 1 This is a flowchart of the method of the present invention;
[0037] Figure 2This is a schematic diagram of the bonding strength of each group in the test examples of the present invention;
[0038] Figure 3 This is a schematic diagram of the anti-permeability pressure of each group in the test examples of the present invention. Detailed Implementation
[0039] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0040] Building exterior walls are exposed to the natural environment for a long time and must withstand multiple effects such as wind and rain erosion, temperature changes, ultraviolet radiation, and acid and alkali corrosion. They are prone to defects such as cracks, hollows, and leaks, which not only affect the integrity of the building's appearance, but also lead to aging of the wall structure, corrosion of steel bars, reduction of the building's service life, and even cause safety hazards.
[0041] Existing exterior wall waterproofing technologies mainly include roll waterproofing, coating waterproofing, and mortar waterproofing. Among them, roll waterproofing is complex to construct, prone to leakage at joints, and has poor adaptability; traditional coating waterproofing (such as silicone coatings and modified bitumen coatings) is convenient to construct, but its crack resistance is insufficient, and irreversible cracks are easily formed due to substrate deformation after long-term use; mortar waterproofing has strong rigidity but poor flexibility, making it difficult to resist the expansion and contraction deformation of the substrate, and once cracks appear, they cannot repair themselves, requiring manual maintenance later, resulting in high maintenance costs and long cycles.
[0042] However, existing self-healing waterproof materials still have significant shortcomings in achieving long-term repair and multi-functional synergy.
[0043] Firstly, some self-healing waterproofing materials achieve crack repair by adding components such as microcapsules and shape memory polymers, but their repair mechanisms have inherent limitations. Microcapsule-type self-healing materials have limited repair agent reserves, which can only achieve single or a few repairs, and cannot meet the needs of long-term service of building exterior walls; the self-healing of shape memory polymers depends on external triggering conditions such as high temperatures, and is difficult to achieve autonomously in natural environments.
[0044] Secondly, existing self-healing coatings are mostly single-function layers, making it difficult to simultaneously achieve waterproofing, weather resistance, and adhesion. Their adhesion strength to the substrate is insufficient, easily leading to hollowing and peeling. Furthermore, their crack resistance is poorly matched with substrate deformation, making it impossible to maintain the integrity and protective stability of the coating structure during long-term service.
[0045] Meanwhile, existing exterior wall waterproofing construction methods suffer from problems such as cumbersome procedures, insufficient targeted treatment of the substrate, low precision in coating thickness control, and non-standard joint treatment, which greatly reduce the overall protective effect of the waterproof coating and make it difficult to fully utilize the performance advantages of waterproof materials.
[0046] In summary, existing building exterior wall waterproofing materials and construction methods have shortcomings in terms of self-repair capability, long-term waterproofing performance, multi-functional synergy, and refined construction control, which restricts the development of exterior wall protection systems towards higher durability, higher reliability, and lower maintenance costs.
[0047] One objective of this invention is to provide a self-healing waterproof composite coating for building exterior walls. The composite coating, from the inside out, consists of a base bonding reinforcement layer, a self-healing waterproof main layer, and a weather-resistant protective surface layer. The raw material composition and properties of each layer are as follows:
[0048] The base bonding reinforcement layer comprises the following raw materials in parts by weight:
[0049] 30-40 parts of waterborne epoxy resin emulsion, 2-4 parts of silane coupling agent (KH-550), 3-5 parts of nano silica (particle size 20-50nm), 25-35 parts of cement-based filler (quartz sand + talc = 1:1), 0.5-1 part of defoamer, 1-2 parts of film-forming aid (propylene glycol methyl ether acetate), and 15-25 parts of deionized water.
[0050] The thickness of the base bonding reinforcement layer is 0.3-0.5 mm, with a bonding strength ≥2.5 MPa (with concrete base) and a water-resistant bonding strength ≥2.0 MPa (after immersion for 72 hours). Waterborne epoxy resin emulsion serves as the film-forming matrix, imparting excellent adhesion properties to the coating. The silane coupling agent (KH-550) and nano-silica work synergistically to penetrate into the capillaries of the base layer, forming a mechanical bond and significantly improving the bonding stability between the composite coating and the base layer. Cement-based filler (a mixture of quartz sand and talc) adjusts the rigidity matching and workability of the coating, preventing hollowing and peeling.
[0051] The self-healing waterproof base layer comprises the following raw materials in parts by weight:
[0052] 40-50 parts of waterborne polyurethane emulsion (solid content ≥60%), 8-12 parts of biodegradable chitosan microcapsules (particle size 100-200μm), 5-8 parts of shape memory polyurethane elastomer (glass transition temperature 25-35℃), 4-6 parts of nano-montmorillonite (modified), 2-3 parts of polyethylene glycol diglycidyl ether (crosslinking agent), 0.5-1 part of UV stabilizer (UV-327), 0.3-0.8 parts of defoamer, and 10-15 parts of deionized water.
[0053] The shape memory polyurethane elastomer is a water-dispersible aliphatic shape memory polyurethane, which is polymerized in three parts: soft segment, hard segment, and hydrophilic chain extender unit. The soft segment is a polyether polyol compounded with polypropylene glycol (PPG-1000) and polyethylene glycol (PEG-1500), which serves as a reversible phase to provide deformation recovery capability. The hard segment is composed of isophorone diisocyanate (IPDI) and 1,4-butanediol, which serve as a stationary phase to form physical crosslinking points and maintain the stability of the coating structure. The hydrophilic unit is neutralized by dimethylolpropionic acid (DMPA) with triethylamine, which allows the elastomer to be stably dispersed in the aqueous phase.
[0054] Nano-montmorillonite was treated with an organic intercalation modification process. The main modifier was hexadecyltrimethylammonium bromide (CTAB, a cationic surfactant), and the auxiliary modifier could be the silane coupling agent KH-550 already included in this system. The total amount of modifier was 1.0-1.2 times the cation exchange capacity of montmorillonite. The specific modification method is as follows:
[0055] 1. Disperse sodium-based nano-montmorillonite in deionized water and prepare a suspension with a mass fraction of 10%-12% by high speed stirring. Heat the suspension to 60-70℃ and maintain the temperature.
[0056] 2. Slowly add the prepared modifier aqueous solution to the suspension and stir continuously for 3-4 hours to insert organic groups into the interlayer of montmorillonite through cation exchange;
[0057] 3. After the reaction is complete, let it stand for 12 hours, then centrifuge and wash repeatedly with deionized water until no bromide ions can be detected in the filtrate;
[0058] 4. After vacuum drying the filter cake, grind and sieve it to obtain modified nano-montmorillonite with expanded interlayer spacing that can be uniformly dispersed in an aqueous system.
[0059] To meet the repair needs of cracks of different widths, biodegradable chitosan microcapsules adopt a bimodal particle size distribution design. Small-sized microcapsules (80-120μm) are mainly distributed on the surface of the coating, providing a rapid response to microcracks with a width of ≤0.3mm. Large-sized microcapsules (150-200μm) are mainly distributed in the middle layer of the coating, releasing more repair agent for cracks with a width of 0.3-0.5mm. The bimodal distribution design ensures the optimal spatial configuration of the repair agent storage, avoiding the problem of excessive release of repair agent in small cracks or insufficient repair agent in large cracks caused by single-sized microcapsules, thereby extending the effective repair cycle while ensuring repair efficiency.
[0060] The self-healing waterproof main layer has a thickness of 1.5-2.5mm, an elongation at break of ≥500%, a seepage resistance of ≥1.2MPa, and low-temperature flexibility (-20℃) without cracks.
[0061] The self-healing waterproof main layer adopts a dual self-healing mechanism: the first healing is immediate microcapsule healing. When cracks occur, the degradable chitosan microcapsules rupture, releasing the encapsulated waterborne polyurethane healing agent, which rapidly cures at the cracks to form a sealing layer, achieving a crack area closure rate of ≥90% for cracks with a width of ≤0.5mm; the second healing is shape memory effect healing. The shape memory polyurethane elastomer can trigger the shape memory effect at natural ambient temperatures (20-40°C), realizing secondary healing of cracks through reversible deformation of molecular chains, achieving a crack area closure rate of ≥85% for cracks with a width of ≤1.0mm, and allowing repeated healing for multiple times.
[0062] The detection method for the crack area closure rate is as follows: a crack induction device is used to generate prefabricated cracks on the coating specimen, a digital microscope is used to capture images of the crack area, and image analysis software is used to calculate the crack area; after the coating undergoes healing and curing, the same area is imaged again and the remaining unclosed crack area is calculated. Healing efficiency (%) = (1 - unclosed crack area after healing / total initial crack area) × 100%. For cracks with a width of ≤0.5mm, a healing efficiency of ≥90% is qualified; for cracks with a width of ≤1.0mm, a healing efficiency of ≥85% is qualified.
[0063] The waterborne polyurethane emulsion serves as the main film-forming substance to construct a flexible waterproof network; the degradable chitosan microcapsules act as the carrier of the healing agent to achieve immediate response when cracks occur; the shape memory polyurethane elastomer endows the coating with repeated healing capability, breaking through the limitation of single healing of traditional microcapsules; the nano-montmorillonite is uniformly dispersed after modification, which can improve the barrier performance and mechanical strength of the coating; polyethylene glycol diglycidyl ether acts as a crosslinking agent to enhance the cohesive strength and water resistance of the coating; the ultraviolet absorber (UV-327) endows the main layer with basic weathering protection capability, and cooperates with the surface layer to extend the service life.
[0064] It should be noted that the degradable chitosan microcapsules use chitosan as the wall material, with the waterborne polyurethane healing agent encapsulated inside. The chitosan wall material has excellent chemical stability in the coating service environment (normal temperature, dry or humid but no crack state), and will not spontaneously degrade or leak; only under the mechanical stress generated by crack propagation, the wall material undergoes brittle rupture and releases the healing agent, so as to achieve immediate sealing and healing at the crack. After the water resistance test (72 hours of immersion), the integrity rate of the microcapsules in the uncracked coating is ≥98%, ensuring their long-term effectiveness in the initial service stage.
[0065] The weather-resistant protective surface layer includes the following raw materials in parts by mass:
[0066] Fluorocarbon emulsion (solid content ≥55%) 35-45 parts, nano titanium dioxide (particle size 10-30nm) 3-5 parts, anti-aging agent (1010) 0.5-1 parts, film-forming aid 1-2 parts, pigment (titanium dioxide) 5-8 parts, deionized water 20-30 parts.
[0067] The thickness of the weather-resistant protective surface layer is 0.4-0.6 mm, and the total thickness of the composite coating is 2.2-3.6 mm. The performance characteristics of the weather-resistant protective surface layer are: resistance to artificial weathering (1000h) without powdering or cracking, qualified resistance to acid and alkali corrosion (immersion for 72h), and surface water absorption rate ≤3%.
[0068] Fluorocarbon emulsion, used as the topcoat substrate, exhibits excellent weather resistance, chemical corrosion resistance, and self-cleaning properties. Nano-titanium oxide effectively absorbs and shields ultraviolet rays while imparting photocatalytic self-cleaning functionality to the coating. An anti-aging agent (1010) further inhibits the thermo-oxidative aging of the material. Titanium dioxide, used as a pigment, provides hiding power and decorative effects. The weather-resistant protective topcoat effectively blocks external factors such as ultraviolet rays, wind, rain, acids, and alkalis from eroding the self-healing waterproof main layer, extending the service life of the composite coating.
[0069] Please see Figure 1 As shown, a second objective of this invention is to provide a construction method for obtaining the aforementioned self-healing waterproof composite coating for building exterior walls, comprising the following steps:
[0070] Step S1: Construction preparation.
[0071] Prepare the materials for each layer in advance according to the above proportions. Stir the base bonding reinforcement layer, self-healing waterproof main layer, and weather-resistant protective surface layer materials evenly, let them stand for 5-10 minutes to remove air bubbles, and use the prepared materials within 1 hour (self-healing waterproof main layer material ≤ 2 hours).
[0072] Step S2: Base layer pretreatment.
[0073] Use a high-pressure cleaner to rinse the base surface to remove loose soil, oil, release agent and loose attachments. Then use a wire brush to clean the remaining impurities. Cut and grind down any protruding parts (protrusion height > 3mm). Cut off and repair any exposed rebar.
[0074] When the crack width is <0.3mm, apply a base bonding reinforcement layer directly for penetration and sealing; when the width is ≥0.3mm, chisel a V-shaped groove (depth ≥10mm, width ≥15mm), fill it with elastic sealant, and then cover it with a layer of 200g / m² alkali-free glass fiber cloth for reinforcement; when the hole diameter is <50mm, fill it with polymer cement mortar in layers (each layer thickness ≤20mm); when the diameter is ≥50mm, insert Φ6 steel bars before repairing.
[0075] After the base layer is dried (moisture content ≤8%, tested by plastic film covering method, no condensation after 24 hours), apply one layer of base treatment agent evenly (dosage 0.2-0.3 kg / m²), and proceed to the next process after it is surface dry (1-2 hours).
[0076] Step S3: Composite coating application.
[0077] Construction of the base bonding reinforcement layer: Apply the coating with a roller in a crisscross pattern, with the thickness controlled at 0.3-0.5mm, ensuring no missed areas or accumulation. Allow to cure naturally for 2-4 hours (surface dry).
[0078] After the bonding reinforcement layer is surface dry, use a special spray gun to spray it. Keep the nozzle 30-50cm away from the wall and move it in an "S" shape. Control the thickness to 1.5-2.5mm and apply it in two coats (0.8-1.2mm for the first coat and 0.7-1.3mm for the second coat). The interval between the two coats should be 4-6 hours (until it is no longer sticky to the touch). For easy-to-leakage nodes such as door and window openings and the base of parapet walls, add an extra layer of fiberglass cloth (overlap width ≥100mm) for reinforcement.
[0079] After the self-healing waterproof main layer has fully dried (24 hours), apply it by roller coating, with the direction perpendicular to the direction of the self-healing waterproof main layer. The thickness should be controlled at 0.4-0.6 mm. Apply two coats with an interval of 1-2 hours. During the application process, use a wet film thickness gauge to check the thickness in real time.
[0080] Step S4: Maintenance and Acceptance.
[0081] After construction, avoid getting water on the wall for 1 day and avoid heavy rain for 7 days. If it rains, cover it with a protective material in time. During the curing period, use a dry and wet alternation curing method (natural curing for the first 2 days, and watering twice a day for the next 5 days). Do not allow external forces to hit the coating.
[0082] The product must be free of cracks, hollow areas, and missed areas in appearance; the thickness deviation must be ±0.2mm; the bonding strength must be ≥2.0MPa; and the impermeability pressure must be ≥1.0MPa. It can only be put into use after passing the acceptance test.
[0083] In this invention, a three-layer structure—a base bonding reinforcement layer, a self-healing waterproof main layer, and a weather-resistant protective surface layer—is designed collaboratively. The materials in each layer complement each other and provide progressive protection. In the base bonding reinforcement layer, the synergistic effect of waterborne epoxy resin emulsion, silane coupling agent, and nano-silica achieves high-strength adhesion and capillary penetration anchoring with the concrete substrate, providing a stable foundation for the composite coating. In the self-healing waterproof main layer, the synergistic effect of waterborne polyurethane emulsion, biodegradable chitosan microcapsules, and shape-memory polyurethane elastomer creates a dual self-healing system that overcomes the limitations of traditional single self-healing technologies, enabling multiple self-repairs for cracks of varying widths. Simultaneously, the introduction of nano-montmorillonite enhances the coating's barrier properties and mechanical strength. In the weather-resistant protective surface layer, the combination of fluorocarbon emulsion and nano-titanium oxide endows the coating with excellent resistance to UV aging, chemical corrosion, and self-cleaning functions, effectively protecting the inner structure.
[0084] The construction method first involves meticulous pretreatment of the substrate, developing differentiated repair plans for different crack widths and hole sizes to provide clean and stable interface conditions for coating application. Subsequently, a step-by-step coating process is adopted, with real-time monitoring of each layer thickness using a wet film thickness gauge. Combined with fiberglass reinforcement at joints, this ensures uniform coating thickness and reliable joint sealing. Finally, alternating wet and dry curing and rigorous acceptance ensure the final quality and long-term service performance of the coating. This method fundamentally overcomes the technical challenges of existing exterior wall waterproofing technologies, such as insufficient crack resistance, lack of self-repair capabilities, and lax construction control, leading to frequent leaks and high maintenance costs. It successfully produces a self-healing waterproof composite coating for building exterior walls that meets high durability and reliability requirements and has a service life of over 15 years.
[0085] The following specific embodiments will further illustrate the construction method and the composite coating of the self-healing waterproof composite coating for building exterior walls provided by the present invention.
[0086] Example 1
[0087] Material preparation:
[0088] 1. Base bonding reinforcement layer (parts by weight): 35 parts water-based epoxy resin emulsion, 3 parts silane coupling agent KH-550, 4 parts nano silica (30nm), 30 parts cement-based filler (quartz sand + talc powder = 1:1), 0.8 parts defoamer, 1.5 parts film-forming aid, and 20 parts deionized water. After stirring evenly, the bonding strength is 2.8MPa, and the water-resistant bonding strength is 2.2MPa.
[0089] 2. Self-healing waterproof main layer (parts by weight): 45 parts water-based polyurethane emulsion (65% solid content), 10 parts biodegradable chitosan microcapsules (150μm), 6 parts shape memory polyurethane elastomer (glass transition temperature 30℃), 5 parts modified nano-montmorillonite, 2.5 parts polyethylene glycol diglycidyl ether, 0.8 parts UV stabilizer UV-327, 0.5 parts defoamer, 12 parts deionized water; elongation at break 550%, impermeability pressure 1.3MPa, closure rate of 88% for 0.8mm crack area;
[0090] 3. Weather-resistant protective surface layer (parts by weight): 40 parts of fluorocarbon emulsion (solid content 58%), 4 parts of nano titanium dioxide (20nm), 0.8 parts of anti-aging agent (1010), 1.5 parts of film-forming aid, 6 parts of titanium dioxide, 25 parts of deionized water. It can withstand artificial weathering for 1000 hours without powdering and has a surface water absorption rate of 2.5%.
[0091] construction:
[0092] For the exterior wall construction of a civil building, the base layer is a concrete wall surface. The construction environment temperature is 25℃ and the relative humidity is 70%. The construction is carried out according to the following steps:
[0093] 1. Base layer pretreatment: High pressure washer washes the wall surface to remove loose soil and oil stains, cuts and grinds the protruding parts (5mm high), repairs the 0.5mm wide crack (V-groove depth 10mm, width 15mm, filled with elastic sealant and covered with fiberglass cloth), the base layer moisture content is tested to be 7%, and the base treatment agent is applied.
[0094] 2. Apply the base bonding reinforcement layer: Apply with a roller in a crisscross pattern, to a thickness of 0.4mm, and allow to cure for 3 hours until surface dry;
[0095] 3. Spray self-healing waterproof main layer: spray in 2 coats. The first coat is 1.0mm thick, and after an interval of 5 hours, spray the second coat with a thickness of 0.9mm. Add fiberglass cloth to door and window openings for reinforcement.
[0096] 4. Apply a weather-resistant protective coating by roller: Apply two coats with a total thickness of 0.5 mm and an interval of 1.5 hours.
[0097] 5. After 7 days of curing, the acceptance test method is as follows:
[0098] Bond strength test
[0099] Based on the pull-out method principle in JG / T25-2017 "Test Method for Temperature Deterioration Resistance of Architectural Coatings" and GB / T5210-2006 "Adhesion Test by Pull-Off Method for Paints and Varnishes": A standard steel pull-out head is attached to the cured coating surface, and a digital display adhesive strength tester is used to apply a vertical tensile force at a uniform speed until failure. The maximum tensile force value at failure is recorded, and the adhesive strength (MPa) is calculated. The dry adhesive strength after 28 days of standard curing and the water-resistant adhesive strength after immersion in water for 72 hours are tested respectively.
[0100] Permeability pressure test
[0101] According to the impermeability test in GB / T16777-2008 "Test Methods for Waterproof Coatings for Buildings", a mortar impermeability test device was used: the specimen (cement mortar substrate) coated with composite coating was placed into the impermeability tester, and water pressure was applied from bottom to top, with 0.1 MPa as the initial pressure, and 0.1 MPa was increased every 24 hours until water seepage appeared on the surface of the specimen. The pressure value at this time was recorded as the impermeability pressure (MPa).
[0102] Crack area closure rate test
[0103] Referring to the crack repair principles in GB / T50448-2015 "Technical Specification for Application of Cement-Based Grouting Materials", concrete specimens with pre-existing cracks were prepared. After the coating was cured, cracks of specific widths (≤0.5mm and ≤1.0mm) were induced using a crack induction device. Crack area closure rate was tested using either an ultrasonic detector to measure crack depth changes or a fluorescent tracer penetrating method to determine crack sealing. Crack area closure rate (%) = (reduction in crack depth after repair / initial crack depth) × 100%, or calculated using image analysis.
[0104] Artificial weathering test
[0105] According to GB / T1865-2009 "Artificial Climate Aging and Artificial Radiation Exposure to Filtered Xenon Arc Radiation for Paints and Varnishes", a xenon arc lamp aging test chamber was used: the coating specimens were placed in the test chamber with an irradiance of 0.51 W / m² (340 nm), a blackboard temperature of (65±3) ℃, a relative humidity of (50±5)%, and water was sprayed periodically to simulate rainfall. After aging for 1000 hours, the powdering, cracking, and peeling of the coating surface were observed, and the color difference and gloss retention rate were tested.
[0106] Service life simulation test
[0107] Referring to the durability cyclic testing methods in JG / T25-2017 and GB / T16777-2008, a combination of accelerated aging and cyclic testing was adopted: the specimens were placed in four environments: ultraviolet aging chamber (60℃, ultraviolet irradiation), salt spray chamber (5% NaCl solution, 35℃ spray), damp heat chamber (70℃, 95% relative humidity), and freeze-thaw cycle (-20℃ to 20℃ alternating). The tests were carried out in sequence. After each cycle (approximately 168 hours), the adhesive strength, impermeability pressure, and appearance integrity of the test coating were measured until the performance indicators dropped to the standard requirements (adhesive strength <1.0MPa or leakage occurred). The number of cycles was recorded, and the equivalent natural service life was calculated by combining the field exposure test data.
[0108] Results: No cracks or hollow areas were found in the appearance; the thickness was 2.8 mm (deviation 0.1 mm); the bond strength was 2.6 MPa (tested according to the pull-out method of JG / T25-2017); and the impermeability pressure was 1.2 MPa (tested according to GB / T16777-2008), meeting the design requirements.
[0109] Test case
[0110] To verify the construction method of the self-healing waterproof composite coating for building exterior walls of this invention, and the synergistic design of the three-layer composite structure consisting of a base bonding reinforcement layer, a self-healing waterproof main layer, and a weather-resistant protective surface layer, as well as the organic integration of the dual self-healing mechanisms (microcapsule instant repair and shape memory effect repair) in the self-healing waterproof main layer, combined with refined construction techniques, which are key to achieving a synergistic improvement in high bonding strength, long-lasting waterproof performance, and self-repair capability, this experimental example, based on the formula and process of Example 1, systematically changes the core technical features and designs the following four sets of comparative experiments:
[0111] Control group D1: No three-layer composite structure group (single coating)
[0112] Solution: Only a self-healing waterproof main layer is used as a single coating, omitting the base bonding reinforcement layer and the weather-resistant protective top layer. The self-healing waterproof main layer is prepared according to the ratio of Example 1, with a thickness controlled at 2.5mm (similar to the total thickness of the three layers in Example 1). The construction process is the same as the spraying steps of the self-healing waterproof main layer in Example 1, without applying the base bonding reinforcement layer or constructing the weather-resistant protective top layer.
[0113] Objective: To establish a performance benchmark and verify the performance of a single self-healing waterproof master layer in terms of bonding strength, weather resistance, and long-term protective performance without introducing a three-layer composite structure.
[0114] Control group D2: Single self-repair mechanism group (microcapsules only)
[0115] Solution: The shape memory polyurethane elastomer is omitted from the self-healing waterproof main layer, and only microcapsules are retained as the sole self-healing mechanism. The amount of shape memory polyurethane elastomer is replaced with an equal amount of water-based polyurethane emulsion, and the remaining components and proportions are the same as in Example 1. The three-layer composite structure and construction process are the same as in Example 1.
[0116] Objective: To isolate and verify the limitations of coatings in repairing multiple cracks, wider cracks, and long-term service when using only the microcapsule single-use repair mechanism.
[0117] Definition and testing methods for multiple repair capabilities:
[0118] Multiple repair capability refers to the coating's ability to self-repair after experiencing an initial crack and subsequent self-repair, and then to self-repair again when cracks appear again. The testing method is as follows:
[0119] ① Initial repair test: Cracks with a width ≤0.5mm were generated on the coated specimen using a crack induction device, and the specimen was cured at a natural ambient temperature (20-40℃) for 72 hours. The initial crack area closure rate was recorded.
[0120] ② Secondary repair test: At the same location after the first repair, a crack with a width ≤0.8mm was generated again using a crack induction device, and the area was left to cure at natural ambient temperature for 72 hours. The secondary crack area closure rate was recorded.
[0121] ③ Repeat the above steps until the coating can no longer effectively repair the crack (crack area closure rate <50% or crack cannot be closed at all), and record the number of times the repair can be repeated.
[0122] The ability to repair multiple cracks is characterized by two indicators: "number of times a crack can be repaired" and "crack area closure rate for a wider crack (0.8 mm) after multiple repairs".
[0123] Control group D3: No node reinforcement and thickness monitoring group (traditional construction)
[0124] Solution: The same material ratio and three-layer structure as in Example 1 are used, but the construction process adopts the traditional method: the V-groove filling reinforcement and fiberglass cloth node reinforcement in the base layer pretreatment are omitted; the self-healing waterproof main layer is applied with a single thick coat (sprayed to 2.5mm in one go), and the thickness is not monitored in real time using a wet film thickness gauge; the curing method adopts natural curing (without dry and wet alternation control).
[0125] Objective: To isolate and verify the impact of refined construction techniques (node reinforcement, layered spraying, thickness monitoring, and alternating wet and dry curing) on coating quality, node sealing reliability, and long-term service performance.
[0126] Control group D4 (Example 1 of the present invention): Complete synergistic structure group
[0127] Solution: The complete solution of this invention is adopted, namely a three-layer composite structure (base bonding reinforcement layer + double self-healing main layer + weather-resistant protective surface layer). The self-healing waterproof main layer includes a dual repair mechanism of microcapsules and shape memory polyurethane elastomer. The construction process includes refined base pretreatment, layered spraying, node reinforcement, real-time monitoring of wet film thickness gauge and alternating dry and wet curing. The specific ratio and process are the same as in Example 1.
[0128] Following the exact same bonding strength testing, permeability pressure testing, crack area closure rate testing, artificial climate aging resistance testing, and service life simulation testing methods described above, the coating samples of the control groups D1, D2, D3, and D4 (Example 1) were tested. Key performance data are compared in Table 1 and... Figure 2 , Figure 3 As shown.
[0129] Table 1 Comparison of experimental performance data
[0130] According to Table 1 and Figure 2 , Figure 3 It can be concluded that:
[0131] The necessity of synergy in three-layer composite structures (comparison between D4 and D1)
[0132] Results: The single-coating group (D1) had a bond strength of only 0.8 MPa and a permeability pressure of 0.7 MPa. After weathering tests, it showed powdering and cracking, and its estimated service life was only 3-5 years, which was significantly lower than that of the complete structure group (D4) of 2.6 MPa, 1.2 MPa and more than 15 years.
[0133] Mechanism: Group D1 relies solely on its self-healing waterproof main layer, which, while possessing a certain degree of flexibility and waterproofing, lacks the chemical anchoring and capillary penetration provided by the base bonding reinforcement layer. This results in weak bonding with the concrete base, making it prone to delamination and detachment. Furthermore, the absence of a weather-resistant protective surface layer exposes the self-healing main layer directly to ultraviolet radiation, wind, rain, acids, and alkalis, accelerating material aging and failure. This invention (D4) achieves a synergistic unity of high-strength bonding and long-term weather resistance through a three-layer structure with complementary functions and progressive protection.
[0134] The necessity of synergistic dual self-healing mechanisms (comparison of D4 and D2)
[0135] Results: Only the microcapsule group (D2) achieved a single crack area closure rate of 92% for cracks ≤0.5mm. However, when faced with wider cracks of 0.8mm and multiple cracking scenarios, due to the limited reserves of microcapsule repair agents and the inability to be repeatedly released, the microcapsules in the D2 group were found to have ruptured completely during the first cracking, making secondary repair impossible. In contrast, the intact structure group (D4) maintained an 88% crack area closure rate for 0.8mm cracks after the second repair, and the test showed that it could be repaired ≥3 times.
[0136] Mechanism: Group D2 relies solely on the immediate repair mechanism of microcapsules. While it can quickly seal initial microcracks, the microcapsules rupture and release the repair agent upon the first cracking, rendering them incapable of repair upon subsequent cracking. This invention (D4) introduces a shape-memory polyurethane elastomer, whose glass transition temperature (25-35°C) matches the ambient temperature. This elastomer can achieve autonomous closure upon crack formation through reversible molecular chain deformation, and this process can be repeated multiple times. The microcapsules are responsible for rapidly sealing immediate cracks, while the shape-memory elastomer continuously responds to repeated cracking. Together, they achieve a functional leap from single-time passive repair to multiple-time active repair.
[0137] The critical importance of refined construction process control (comparison between D4 and D3)
[0138] Results: The thickness deviation of the traditional construction group (D3) reached ±0.8mm, the joint leakage was obvious, the seepage pressure was only 0.9MPa, and the service life was 6-8 years. All indicators were significantly inferior to the complete construction process group (D4).
[0139] Mechanism: The single-coat thick coating used in group D3 prevents sufficient expulsion of air bubbles within the coating, leading to stress concentration points during curing shrinkage and increasing the risk of microcracks. The omission of V-groove filling and joint reinforcement makes cracks and joints vulnerable to leakage. The lack of real-time monitoring of wet film thickness results in uneven thickness and reduced localized protective capabilities. Natural curing methods cannot guarantee sufficient hydration and stress release. This invention (D4) ensures coating density through layered spraying, eliminates leakage risks through refined joint reinforcement, ensures uniformity across layers through real-time thickness monitoring, and promotes full material performance development through alternating wet and dry curing, fundamentally guaranteeing the final coating quality and long-term service reliability.
[0140] The comparative experiments of the above systems fully demonstrate that the three-layer composite structure design of the base bonding reinforcement layer, the self-healing waterproof main layer, and the weather-resistant protective surface layer proposed in this invention, the integration of the dual self-healing mechanisms of microcapsule instant repair and shape memory effect repair in the self-healing waterproof main layer, and the refined construction process (layered spraying, node reinforcement, thickness monitoring, and alternating dry and wet curing), constitute an organically synergistic and indispensable technical system. This design successfully solves the chain reaction problems of frequent leakage and high maintenance costs caused by insufficient crack resistance, inability to self-repair, and rough construction control in traditional external wall waterproofing technology. The absence of any single feature will lead to a significant and observable degradation in the waterproof coating's key bonding strength, repair capability, weather resistance, or construction quality indicators.
[0141] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely preferred examples and are not intended to limit the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the present invention as claimed. The scope of protection of the present invention is defined by the appended claims and their equivalents.
Claims
1. A construction method for a self-healing waterproof composite coating for building exterior walls, characterized in that, Includes the following steps: Step S1: Weigh the materials of each layer according to their mass percentages. Each layer of materials includes the base bonding reinforcement layer, the self-healing waterproof main layer, and the weather-resistant protective surface layer. Specifically: The base bonding reinforcement layer includes 30-40 parts of waterborne epoxy resin emulsion, 2-4 parts of silane coupling agent, 3-5 parts of nano silica, 25-35 parts of cement-based filler, 0.5-1 part of defoamer, 1-2 parts of film-forming aid, and 15-25 parts of deionized water. The self-healing waterproof main layer consists of 40-50 parts of water-based polyurethane emulsion, 8-12 parts of biodegradable chitosan microcapsules with a particle size of 100-200μm, 5-8 parts of shape memory polyurethane elastomer, 4-6 parts of nano-montmorillonite, 2-3 parts of polyethylene glycol diglycidyl ether, 0.5-1 part of UV stabilizer, 0.3-0.8 parts of defoamer, and 10-15 parts of deionized water. The weather-resistant protective surface layer consists of 35-45 parts of fluorocarbon emulsion, 3-5 parts of nano titanium dioxide, 0.5-1 part of anti-aging agent, 1-2 parts of film-forming aid, 5-8 parts of pigment, and 20-30 parts of deionized water. Stir each layer of material thoroughly and let it stand to remove air bubbles; Step S2: Base layer pretreatment, clean the base layer surface, treat cracks and holes, and apply base treatment agent after the base layer is dry; Step S3: Composite coating construction, the base bonding reinforcement layer, the self-healing waterproof main layer and the weather-resistant protective surface layer are constructed in sequence. The self-healing waterproof main layer is sprayed in two coats, and fiberglass cloth is added to the joints for reinforcement. Step S4: Maintenance and acceptance. After the construction is completed, maintenance shall be carried out, and the equipment shall be put into use after passing the acceptance.
2. The construction method of the self-healing waterproof composite coating for building exterior walls according to claim 1, characterized in that: In step S1, the settling time is 5-10 minutes, the prepared material must be used up within 1 hour, and the self-healing waterproof main layer material must be used up within 2 hours.
3. The construction method of the self-healing waterproof composite coating for building exterior walls according to claim 1, characterized in that: In step S2, a high-pressure cleaner is used to rinse the surface of the base layer to remove loose soil, oil stains, release agent and loose attachments. Then, a wire brush is used to clean the remaining impurities. For areas with a protrusion height > 3mm, the surface is cut and ground flat. Exposed parts of the reinforcing bars need to be cut off and repaired. When the crack width is <0.3mm, directly apply the base bonding reinforcement layer for penetration and sealing. When the width is ≥0.3mm, chisel a V-shaped groove with a depth ≥10mm and a width ≥15mm, fill it with elastic sealant, and then cover it with a layer of 200g / m² alkali-free glass fiber cloth for reinforcement. When the hole diameter is <50mm, fill it in layers with polymer cement mortar. When the diameter is ≥50mm, insert Φ6 steel bars and then repair it. After the base layer is dry, apply one layer of base treatment agent evenly. After the surface is dry, proceed to the next process.
4. The construction method of the self-healing waterproof composite coating for building exterior walls according to claim 3, characterized in that: In step S2, the moisture content of the base layer is detected by covering with a plastic film. If there is no condensation after 24 hours, the moisture content is determined to be ≤8%. The dosage of the base layer treatment agent is 0.2-0.3 kg / m², and the surface drying time is 1-2 hours.
5. The construction method of the self-healing waterproof composite coating for building exterior walls according to claim 1, characterized in that: In step S3, the base bonding reinforcement layer is applied by roller in a crisscross pattern, with the thickness controlled at 0.3-0.5 mm. After application, it is allowed to cure naturally for 2-4 hours until it is surface dry. The self-healing waterproof main layer is applied using a special spray gun. The nozzle should be 30-50cm away from the wall and moved in an "S" shape. The thickness should be controlled at 1.5-2.5mm, with the first coat being 0.8-1.2mm and the second coat being 0.7-1.3mm. The interval between the two coats should be 4-6 hours. After the self-healing waterproof main layer has fully dried, the weather-resistant protective top layer is applied by roller coating, with the direction perpendicular to the coating direction of the self-healing waterproof main layer. The thickness is controlled at 0.4-0.6mm, and it is applied in 2 coats with an interval of 1-2 hours. During the coating process, the thickness is monitored in real time using a wet film thickness gauge.
6. The construction method of the self-healing waterproof composite coating for building exterior walls according to claim 5, characterized in that: In step S3, the ambient temperature during construction is controlled between 5-35℃, the relative humidity is ≤85%, there is no rain or strong wind, and an infrared thermometer is used to monitor the wall temperature in real time to avoid construction at a wall temperature >40℃ or at low temperatures. The pressure of the special spray gun is 0.8-1.2 MPa; The interval between two coats of the self-healing waterproof main layer should be determined by whether it is sticky to the touch.
7. The construction method of the self-healing waterproof composite coating for building exterior walls according to claim 1, characterized in that: In step S3, an additional layer of 200g / m² alkali-free fiberglass cloth is laid at the door and window openings and at the base of the parapet wall, with an overlap width of ≥100mm.
8. The construction method of the self-healing waterproof composite coating for building exterior walls according to claim 1, characterized in that: In step S4, avoid getting water on the wall for 1 day after construction and avoid heavy rain for 7 days. During the curing period, adopt a dry and wet alternation curing method of natural curing for the first 2 days and watering twice a day for the next 5 days. External force collision with the coating is prohibited.
9. The construction method of the self-healing waterproof composite coating for building exterior walls according to claim 1, characterized in that: In step S3, the weather-resistant protective surface layer is applied after the self-healing waterproof main layer has been fully dried for 24 hours.
10. A self-healing waterproof composite coating for building exterior walls obtained by the construction method according to any one of claims 1-9, characterized in that, The composite coating consists of, from the inside out, a base bonding reinforcement layer, a self-healing waterproof main layer, and a weather-resistant protective top layer, with a total thickness of 2.2-3.6 mm. The thickness of the base bonding reinforcement layer is 0.3-0.5 mm, the bonding strength is ≥2.5 MPa, and the water-resistant bonding strength is ≥2.0 MPa; The thickness of the self-healing waterproof main layer is 1.5-2.5mm, the elongation at break is ≥500%, the seepage resistance pressure is ≥1.2MPa, and it is flexible at low temperature -20℃ without cracks. The thickness of the weather-resistant protective surface layer is 0.4-0.6mm. It can withstand artificial weathering for 1000h without powdering or cracking, and its performance in acid and alkali corrosion immersion for 72h is qualified. The surface water absorption rate is ≤3%.